2003
DOI: 10.1177/147078530304500103
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Brand Trust Scale

Abstract: To enrich the limited and recent work in existence on relational phenomena in the consumer-brand domain, the authors focus on the concept of brand trust. The non-existence of a wider accepted measure of this concept is surprising given that: (1) trust is viewed as the cornerstone and one of the most desired qualities in a relationship; and (2) it is the most important attribute a brand can own. In this context, this research reports the results of a multi-step study to develop and validate a multidimensional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(144 citation statements)
references
References 51 publications
1
80
0
6
Order By: Relevance
“…According to Roberts [22], brand love represented the consumer's feeling and emotion to the brand (emotional attributes), including mystery (customer's aspirations, goals, dreams, stories, and myths on a brand that are beyond rationality and calculation), sensuality (perceptions formed through consumer's five senses: Sound, sight, smell, touch, and taste), and intimacy (the degree of commitment, empathy, and passion that consumers have on a brand). Further, brand respect refers to consumer's perceptions of brand function and performance (functional attributes), including performance (market share, brand value, and the innovation and superiority of brand quality) [16,58], reputation (the actual degree of commitment fulfilling a brand has provided to consumers) [58], and trust (consumer's sense of security in the process of interacting with a brand) [59]. Although the lovemarks express the intense feelings of the consumer for a specific brand, the premise of brand love is brand respect since it is the basis for maintaining a long-term relationship [22,60].…”
Section: Lovemarksmentioning
confidence: 99%
“…According to Roberts [22], brand love represented the consumer's feeling and emotion to the brand (emotional attributes), including mystery (customer's aspirations, goals, dreams, stories, and myths on a brand that are beyond rationality and calculation), sensuality (perceptions formed through consumer's five senses: Sound, sight, smell, touch, and taste), and intimacy (the degree of commitment, empathy, and passion that consumers have on a brand). Further, brand respect refers to consumer's perceptions of brand function and performance (functional attributes), including performance (market share, brand value, and the innovation and superiority of brand quality) [16,58], reputation (the actual degree of commitment fulfilling a brand has provided to consumers) [58], and trust (consumer's sense of security in the process of interacting with a brand) [59]. Although the lovemarks express the intense feelings of the consumer for a specific brand, the premise of brand love is brand respect since it is the basis for maintaining a long-term relationship [22,60].…”
Section: Lovemarksmentioning
confidence: 99%
“…Trust scale was taken from Munuera-Aleman et al (2003) and adapted to the research with four items. Loyalty scale, which was a four-item scale, was modified from Munuera-Aleman et al (2003). e-Wom scale, which had nine items, was adapted from Goyette et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…In literature, mostly the effects of e-WOM on consumers' buying behavior were investigated (Park and Lee, 2008;Amblee and Bui, 2011;Ladhari and Michaud, 2015;Babic Rosari et al, 2016). However, in this study, it was aimed to analyze the effects of trust, which was found as one of the antecedents of loyalty (Chaudhuri and Holbrook, 2001;Munuera-Aleman 2003), and loyalty on e-WOM activities. Within this aim, the hypotheses were developed as follow:…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the evolving number of crisis and unethical practices used by some firms as well as the importance of confidence in warranting the exchange's stability (Gatfaoui and Lavorata, 2001) [36], reducing the doubt in volatile environment (Chaudhuri and Holbrook, 2001) [37] and securing clients (Georges and Decock Good, 2004) [38]. In this regard, Bainbridge (1997, p13) [39] asserted that "a trustworthy brand places the consumer at the center of its world and relies more on understanding real consumer M. Trabelsi DOI: 10.4236/ojbm.2020.82027 433 Open Journal of Business and Management needs and fulfilling them than the particular service or product. It is not merely responsive, but responsible".…”
Section: Brand Trustmentioning
confidence: 99%
“…The first group is based on rational drivers grounded on the brand competence, its reputation, its willingness to keep its promises, its ability to raise up the customer pleasure and comfort, to satisfy them, to keep in pace with their evolving requirements and to reassure them by controlling the sources of the brand's perceived risk. In fact, Blomqvist, Ballester and Aleman (2000) [39] have postulated that the main condition of the creation of the brand trust is the perceived risk, its depth and nature; the more the risk is present, the more the development of the confidence feeling is hard and unexpected. The second category of BT antecedents is composed of factors signaling perceived common points between the consumer and his/her brand.…”
Section: Brand Trustmentioning
confidence: 99%